KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 9 PADANG - Ikhsan, Hafizul; Basri, Irfani (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT The purpose of this study is three. First, describing reading skills understanding the text description of class VII students of SMP Negeri 9 Padang. Second, describe the writing skills of description text. Third, describe the correlation of reading text description understanding with writing text description skills of class VII students of SMP Negeri 9 Padang. The population of this study was seventh grade students of SMP Negeri 9 Padang who were registered in the 2019/2020 school year with 192 students. The sample in this study was determined by proportional random sampling of 25% of the population, which is 48 students. Based on data analysis and discussion, three research results are obtained as follows. First, reading skills understanding the text description of class VII students of SMP Negeri 9 Padang in good qualifications. This can be seen from the acquisition of a calculated average of 78,39. Second, the writing text description skills of class VII students of SMP Negeri 9 Padang are in good qualification. This can be seen from the acquisition of a calculated average of 82,20. Third, there is a significant correlation between reading skills in the description of text description and writing text description skills of class VII students of SMP Negeri 9 Padang in the n-1 freedom degree and 95% significant level. H0 is rejected and H1 is accepted because the test results prove that the tcount is greater than t table, namely (6,72> 1.68). Kata Kunci: Korelasi, Keterampilan Membaca Pemahaman, Keterampilan Menulis Teks Deskripsi